Bringing together the 'Threads of Care' in possible miscarriage for women, their partners and nurses in non-metropolitan EDs. Issue 3 (June 2018) - Edwards, Susan; Birks, Melanie; Chapman, Ysanne; Yates, Karen
Abstract: Background: Pregnancy is a significant event in a woman's life, a time of great expectation and attachment to the possibilities and dreams placed onto the new life growing inside her. Complications in pregnancy are physically and psychologically traumatic experiences that can generate high levels of anxiety. Vaginal bleeding, pain, or both in the first trimester of pregnancy are common causes for presentation in any Australian emergency department. These emergency departments play an important role in the provision of healthcare in regional, rural and remote areas. When experiencing possible miscarriage, the care that is provided to women and their partners presenting to their regional, rural and remote emergency departments can have significant impact on their approach to current and future pregnancies. Aim: The aim of this research was to explore the experiences of women and male partners who presented to non-metropolitan emergency departments with possible miscarriage, along with the experiences of nursing staff who provided care in these settings. Methods: Using a grounded theory methodology, three participant groups were included in this study: women who presented to an emergency department, their partners, and the nursing staff who provided care in these settings. Findings: The developed theory 'Threads of Care' incorporated five stages of their journey through a non-metropolitan emergency department with possible pregnancy loss: presenting as one; wanting recognition and inclusion; seeking support and understanding; leaving as one; and moving on. Discussion: The theory enhances the understanding of what constitutes optimal and effective care for women and their partners when presenting to non-metropolitan emergency departments with possible miscarriage. Conclusion: The recommendations from this grounded theory will inform approaches to care that aim to meet the needs of women, their partners and nursing staff who care for them.